Construction of hierarchical Prussian Blue Analogue phosphide anchored on Ni2P@MoOx nanosheet spheres for efficient overall water splitting. (5th May 2020) - Wang, Fangmu; Qi, Xiaopeng; Qin, Zhengguang; Yang, Hui; Liu, Chao; Liang, Tongxiang
Abstract: In response to the energy crisis, molybdenum-based catalyst has been proposed as a high-performance electrocatalytic material due to its low price and excellent HER performance. However, in contrast with its excellent HER performance, its poor OER performance often limits practical application as a high-performance overall water splitting catalyst. In this study, Prussian blue analogue (PBA) is grown in-situ on molybdenum-based nanosheet spheres by a simple and ingenious method and then subjected to phosphorization. The resulting composite catalyst exhibits highly efficient overall water splitting performance, overpotentials at current densities of 10 mA cm −2 and 100 mA cm −2 for the HER and OER are −61 mV and 268 mV, respectively. Moreover, an alkaline electrolyzer makes up by the catalyst both as positive and negative can reach a cell voltage 1.494 V at 10 mA cm −2 for the overall water splitting. This method has provided a new strategy to effective combine PBA and molybdenum-based catalyst. Graphical abstract: Image 1 Highlights: Prussian Blue Analogue (PBA) in-situ grow on Molybdenum-based nanosheet spheres. OER performance of catalysts greatly improved by PBA anchoring. It provided a strategy to combine the PBA and matrix effectively.